2023
DOI: 10.1038/s41598-023-28108-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-4 with pachychoroid neovasculopathy

Abstract: The purpose of this study was to identify the inflammatory cytokines that were associated with pachychoroid neovasculopathy (PNV). Seventy-five eyes of 75 patients with PNV, 145 eyes of 145 patients with neovascular age-related macular degeneration without pachyvessels, and 150 eyes of 150 normal subjects were examined for the levels of intraocular cytokines. In eyes with PNV, the levels of IL-1α, IL-1β, IL-2, IL-4, IL-10, and VEGF were significantly higher than that of the controls. Logistic regression analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The eluted tear uid samples were analyzed for the levels of IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-13, IL-15, IL-17, IFN-γ, TNF-α, TNF-β, VEGF, and CCL2 using a commercial ELISA kit (Quansys Biosciences; West Logan, UT). In addition, the PeproTech (Rocky Hill, NJ) was used for CCL2, and the R&D Systems (Minneapolis, MN) for VEGF [9,10,18,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eluted tear uid samples were analyzed for the levels of IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-13, IL-15, IL-17, IFN-γ, TNF-α, TNF-β, VEGF, and CCL2 using a commercial ELISA kit (Quansys Biosciences; West Logan, UT). In addition, the PeproTech (Rocky Hill, NJ) was used for CCL2, and the R&D Systems (Minneapolis, MN) for VEGF [9,10,18,19].…”
Section: Methodsmentioning
confidence: 99%
“…The results of recent studies have indicated that in ammatory cytokines may play a role in the pathogenesis of vaso-proliferative diseases [9,10] including ROP [11]. The tear uid has been a source of biomarkers for ocular diseases [12,13], and it is easily accessible and can be collected non-invasively [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PeproTech (Rocky Hill, NJ) was used for CCL2, and the R&D Systems (Minneapolis, MN) for VEGF. 9,39,45 Statistical analyses Logistic regression analyses and linear regression analyses were performed to calculate the odds ratios (OR) and coe cients based on quantiles of each cytokine level. Each tear uid cytokine quantile was compared with the lowest quantile as the reference category.…”
Section: Measurement Of Cytokines In Tear Uidmentioning
confidence: 99%